Myomectomy: Choosing the Surgical Approach - A Systematic Review - Jhanice Sangdaan Paredes; Chyi-Long Lee; Peng Teng Chua (Wolters Kluwer Medknow Publications, 2024)
Myomectomy has evolved from open laparotomy to laparoscopy, hysteroscopy, VNOTES and robotic myomectomy. The surgical approach in doing myomectomy depends on the type and location of the myoma and the surgeon's expertise. Minimally invasive surgery has been the preferred approach due to the benefit of shorter hospital stay, lesser postoperative pain, earlier recovery, minimal blood loss and the cosmetic appearance of the scar. The success of this procedure depends on the incision technique, enucleation, and blood loss prevention by using hemostatic techniques and suturing techniques. Performing myomectomy for a large uterine myoma is a laparoscopic challenge; however, with the use of Lee-Huang point (midpoint between umbilicus and xiphoid) as the primary insertion and camera port, one can easily navigate thru the abdominal cavity in case the uterus is huge obscuring the umbilical port. Laparoscopic Myomectomy can be safely and efficiently performed by experienced laparoscopic surgeons regardless of myoma size, number and location. Removal of large myoma specimen from the abdominal cavity through the laparoscope became a challenge after the use of power morcellator was abandoned. To overcome this problem, the large myoma is placed inside an Endo bag and its edges brought extracorporeally through the port site. The myoma is incised in a C-manner using a scalpel to reduce the size. Myoma can also be removed using in-bag power morcellation. Fertility preservation is the long-term aim of doing myomectomy instead of hysterectomy in the management of leiomyoma aside from alleviating symptoms of abnormal uterine bleeding, urinary frequency and abdominal pain.